Interactive Content for High School Students in Bali with a Multimedia Graphic Design Approach - Mouren Yunni Esther Pua; I Nyoman Anom Fajaraditya Setiawan; Made Dona Wahyu Aristana (Eduvest - Journal of Universal Studies, 2025)
Education in the digital age faces significant challenges in delivering informative and engaging material to students. In Indonesia, particularly in Bali, many high schools are working to integrate technology into the curriculum to improve student engagement and learning quality. One popular tool used is Canva, a graphic design platform that allows users to easily create engaging visual content. This research aims to explore innovations in multimedia graphic design with a focus on the use of the Canva design tool and its impact in interactive content development for high school students in Bali. Qualitative research methods were used to conduct a case study of Canva's implementation in the creation of interactive content for online learning in several high schools in Bali. The results show that the use of Canva as a multimedia graphic design tool makes a positive contribution in creating interactive content that is interesting and easily understood by students. The findings show Canva's great potential in supporting multimedia graphic design innovation in educational contexts, as well as addressing student engagement issues and making it easier for teachers to present interesting and interactive materials.